Carbon and natural fiber reinforced polymer hybrid composite: Processes, applications, and challenges - J. Shewale; C. Choudhari; A. Bankoti (Journal of Mechanical Engineering and Sciences, 2022)
Composites have recently emerged as the ideal material for weight reduction in a wide range of technical applications. Hybrid composites offer special properties that enable them to meet a wide range of design objectives more efficiently and affordably than conventional composites. Natural fiber-based hybrid composites are also less damaging to the environment and have a reduced carbon footprint. The hybridization of natural fibres with synthetic fibres can substantially minimise the problems associated with natural fibre composites, since the advantages of one kind of fibre can outweigh the disadvantages of another. Several research have been carried out to investigate the different characteristics of carbon-natural fibre reinforced hybrid composites and to evaluate their suitability for a variety of technological applications. The objective of this work is to provide an overview of the materials and manufacturing processes currently utilised to fabricate carbon-natural fibre reinforced hybrid composites. This paper also attempts to discuss the reported mechanical, damping, and other characteristics of the resultant hybrid composites. This article provides a factual overview of the development accomplished so far in the field of hybrid composites constructed from carbon-natural fibres.